2018
DOI: 10.1111/phn.12571
|View full text |Cite
|
Sign up to set email alerts
|

Cancer site differences in the health‐related quality of life of Korean cancer survivors: Results from a Population‐based Survey

Abstract: Objectives:We investigated cancer site differences in the health-related quality of life (HRQOL) of cancer survivors. Design and Sample: A secondary data analysis was conducted using the sixth KoreaNational Health and Nutrition Examination Survey (2013)(2014)(2015). Participants were 15,461 adults (664 cancer survivors) with available EuroQol-5 Dimensions (EQ5D) information.Measurements: Constructs from the revised Wilson and Cleary's model were examined. HRQOL status was measured using the EQ5D. EQ5D dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…However, these findings were not uniformly demonstrated across studies. The impact of TC on HRQoL varied widely; while a small number of studies demonstrated no long-lasting HRQoL detriments in TC survivors compared with the general population (41,42,44), others reported comparable or worse HRQoL to other cancer types with significantly worse prognoses (34,36,38)-a finding previously demonstrated by others (54).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, these findings were not uniformly demonstrated across studies. The impact of TC on HRQoL varied widely; while a small number of studies demonstrated no long-lasting HRQoL detriments in TC survivors compared with the general population (41,42,44), others reported comparable or worse HRQoL to other cancer types with significantly worse prognoses (34,36,38)-a finding previously demonstrated by others (54).…”
Section: Discussionmentioning
confidence: 79%
“…Of the 28 included studies, 17 demonstrated impaired HRQoL in TC survivors compared with age-and sex-matched controls (40), the general population (21,30,34,36,43), or survivors of other types of cancer (34,36,38). Only three studies reported no decrease in HRQoL in TC survivors (41,42,44).…”
Section: Qol In Tc Survivorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, patients with thyroid cancer felt negative feelings and isolation about the fact that thyroid cancer represented as good cancer [19]. Patients with thyroid cancer experience high levels of distress and worry, despite having a good prognosis, and have more prevalent anxiety and depression than other cancers [20][21][22]. Cancer patients feel psychological pain such as anxiety and depression and seek social support [23].…”
Section: Introductionmentioning
confidence: 99%
“…Six studies (seven publications) [35,38,44,48,50,51,53] measured HRQoL using the EQ-5D-3L. In 23 studies, HRQoL was measured using either the SF-36 or the EORTC QLQ-30 and therefore mapping to the EQ-5D-3L was required (which comprised of 29 publications) [9, 18-34, 39-43, 45, 52, 54-57].…”
Section: Resultsmentioning
confidence: 99%